Kreativitas Dan Kompetensi Guru Sekolah Dasar - Sri Judiani (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
This study is aimed at knowing whether or not there is a correlation between creativity and primary teachersâ€™ competence. The study was conducted in the primary schools in Central Jakarta during the first semester of the academic year 2008/2009. The method used in the study is a survey with the correlation technique. The population of the study is primary school teachers. The total number of respondents is sixty, consisting of grade III, IV and grade V teachers, choosing them by using multy stage random sampling. The verbal creativity test standardized by the Faculty of Psychology of Indonesia University was also be used to measure the degree of creativity of primary school teachers whereas for measuring the primary school teachers competence, the head-teachers use a guide of teacher observation and its items refer to the standardized competences for primary school teachers. Because the two instruments are standardized and that became the reason for not conducting the try-out of the two in order to know their validity and reliability. The technique used to analyze the data were correlation and regression. The data of study shows that there is a positive and significant correlation between the creativity and the competence of the primary school teachers, and its degree of correlation is shown by coefficient correlation ry = 0.704. Coefficient determination (ry2) is 50 meaning that the creativity has relatively supported 50% to the primary school teachers. With other words, the competence of the primary school teachers can be enhanced by enhancing their own creativity.Â ABSTRAKÂ Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara kreativitas dengan kompetensi guru SD. Penelitian dilakukan di SD wilayah Jakarta Pusat, pada semester 1 tahun ajaran 2008/2009. Metode penelitiannya adalah survei dengan teknik korelasional. Populasi penelitian adalah guru SD wilayah Jakarta Pusat, jumlah sampelnya 60 orang guru SD kelas III, IV, dan V yang diambil dengan teknik multystage random sampling.Untuk mengukur kreativitas guru SD digunakan Tes Kreativitas Verbal yang dibakukan penggunaannya di Indonesia oleh Fakultas Psikologi Universitas Indonesia. Untuk mengukur kompetensi guru SD digunakan Panduan Observasi Guru oleh Kepala Sekolah, yang mengacu pada Standar Kompetensi Guru SD. Karena kedua instrumen merupakan instrumen baku maka tidak dilakukan uji validitas dan reliabilitas. Teknik analisis data yang digunakan adalah korelasi dan regresi. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara kreativitas dengan kompetensi guru SD, kadar hubungannya ditunjukkan oleh koefisien korelasi sebesar ry = 0,704. Koefisien determinasinya (ry2) sebesar 50 yang berarti kreativitas memberikan sumbangan relatif sebesar 50% terhadap kompetensi guru SD. Dengan kata lain, kompetensi guru SD dapat ditingkatkan dengan cara meningkatkan kreativitasnya.